2017
DOI: 10.1590/1517-869220172304163788
|View full text |Cite
|
Sign up to set email alerts
|

Muscle Strength, Gh and Igf-1 in Older Women Submitted to Land and Aquatic Resistance Training

Abstract: Introduction: Aging leads to decline in multiple organ systems associated to hormone alterations and loss of muscle mass and strength. Objective: To evaluate the effects of land and water resistance training on muscle strength, basal serum levels of GH, IGF-1, and IGFBP3 in elderly women. Methods: Subjects were distributed in three groups: land resistance training (LRT; n=10; age: 66.10±2.77 years), water resistance training (WRT; n=10; age: 67.10±3.54 years) and control (CG; n=10; age: 68.80±5.41 years). Musc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 28 publications
0
7
0
1
Order By: Relevance
“…Similar results have been observed with resistance training. A 12-week resistance training intervention in older (mean age > 60 years old) sedentary women resulted in an increase in IGF-1 levels (Vale et al 2017), and increased IGF-1 was positively related with cognitive function in older adults after a 52-week intervention (Tsai et al 2015), and after a 24-week intervention in 62 sedentary elderly (Cassilhas et al 2007a).…”
Section: Exercise-induced Igf-1 Increase In Blood Flow and Cognitionmentioning
confidence: 99%
“…Similar results have been observed with resistance training. A 12-week resistance training intervention in older (mean age > 60 years old) sedentary women resulted in an increase in IGF-1 levels (Vale et al 2017), and increased IGF-1 was positively related with cognitive function in older adults after a 52-week intervention (Tsai et al 2015), and after a 24-week intervention in 62 sedentary elderly (Cassilhas et al 2007a).…”
Section: Exercise-induced Igf-1 Increase In Blood Flow and Cognitionmentioning
confidence: 99%
“…A total of 1066 studies were found (Supplementary Fig. 1), and 179 potentially includable studies were identified through the title and abstract, of which 30 RCTs [17,[23][24][25] met the eligibility criteria and were included in the systematic review; of these, 27 were included in the meta-analysis [17,23,[30][31][32][33][34][35][36][37][38][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55] (3 were excluded because no data were available).…”
Section: Study Selectionmentioning
confidence: 99%
“…A total of 30 RCTs [16,[23][24][25][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48] published between 1994 and 2021 involving 1247 subjects (664 women; 53.25%) aged 45 to 92 years were included in the systematic review. The RCTs were conducted in the following continents: Oceania [39], Asia [17,32,33,42,44,48,50], Europe [24,31,41,43,45,46,52] and America [23,25,30,[34][35][36][37][38]40,47,49,[53]…”
Section: Study and Intervention Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Maiores níveis de IGF-1 trazem benefícios a idosas, sendo relevante o conhecimento de meios que aumentem sua síntese e liberação Oliveira et al, 2003). O treinamento de força auxilia no incremento dos níveis hormonais de IGF-1 (Vale et al, 2017a;Vale & Rodrigues, 2014;Bastos et al, 2013;Vale et al, 2009). Os exercícios no meio aquático podem ser uma alternativa aos exercícios terrestres, apresentando menos estresse nas articulações e menor risco de quedas quando comparado ao ambiente terrestre (Hale, Waters, & Herbison, 2012).…”
Section: Introductionunclassified